Language tree divergence times support the Anatolian theory of Indo-European origin - Gray, R; Atkinson, Q (Nature Publishing Group, 2003)
Languages, like genes, provide vital clues about human history. The origin of the Indo-European language family is 'the most intensively studied, yet still most recalcitrant, problem of historical linguistics'. Numerous genetic studies of Indo-European origins have produced inconclusive results. Here we analyse linguistic data using computational methods derived from evolutionary biology. We test between two theories of Indo-European origin - the 'Kurgan expansion' and 'Anatolian farming' hypotheses. The former centres on possible archaeological evidence for an expansion into Europe and the near-East by Kurgan horsemen beginning in the sixth millennium BP. The latter claims that Indo-European languages expanded with the spread of agriculture from Anatolia around 8,000 to 9,500BP. In striking agreement with the Anatolian hypothesis, our analysis of a matrix of 87 languages with 2,449 lexical items produced an estimated age range for the initial Indo-European divergence of between 7,800BP and 9,800BP. The results were robust to changes in coding procedures, calibration points, rooting of the trees and priors in the Bayesian analysis.